Perkembangan Penalaran Moral Anak Laki-Laki dan Perempuan di Madrasah Ibtidaiyah Dhiya El Haq Cirebon - Azis, Ahmad Azis Badruudin Abdussallam; Septi Gumiandari, Septi Gumiandari (TSAQAFATUNA : Jurnal Ilmu Pendidikan Islam, 2025)
AbstractMoral reasoning is a crucial aspect of character development among students, particularly at the elementary Islamic school level (madrasah ibtidaiyah). This study is motivated by indication of differences in the level of moral development between male and female students at MI Dhiya El Haq Cirebon, focusing on six key aspects: honesty, discipline, responsibility, politeness, empathy, and self-confidence. Employing a qualitative phenomenological approach, the study explores the dynamics of moral reasoning among fifth- and sixth-grade students. Data were collected through observation, interviews, and documentation. The findings indicate that both boys and girls generally exhibit moral reasoning at the pre-conventional to early conventional stages. Although they are at similar developmental levels, girls display greater stability in moral aspects, particularly honesty and social empathy. Similarities were found in the situational nature of moral behavior and the generally low levels of responsibility and confidence in expressing opinions. However, significant differences reveal that girls tend to be more morally independent, while boys remain more dependent on external guidance.